Prospective Model in Public Policy for a Democratic and Equitable Election of Regional Leaders - Suparnyo Suparnyo (Universitas Muhammadiyah Sidoarjo, 2020)
The election of regional leaders conducted directly by the community is believed to result in a democratic government. The formed government is expected to be more open, more responsive, and to carry out the aspirations of the people so that it can realize a government that comes from the people, by the people, and for the people. A person can nominate him/herself as a candidate for Regent or Deputy Regent if supported by some residents, by Political Parties or Combined Political Parties. The relatively weak support of the population or political parties or combined political parties has resulted in very few candidates for regent or deputy regent, even only one pair of candidates can occur as in Pati Regency. The study aims to know how the policy in the future (Prospective Model) should be taken so that the single-candidate for Regent or Deputy Regent in a general election does not happen. By using a sociological juridical approach, collecting primary and secondary data, processing and analyzing data, the objective of the study can be reached.The policy that needs to be taken by the government so that in the future there will be no single candidate is by giving obligations to political parties to conduct cadre recruitment to become candidates for regional leaders. Besides, the General Election Commission needs to make a scheme that is easier and more flexible for individual candidates regarding administrative requirements, procedures, and mechanisms for gathering support, and there needs to be a new policy so that the potential for a single-candidate can be eliminated or not occur.